A new and critical edition of George Osborn's The poetical Works of John and Charles Wesley (1868-1872). Volume III with the addition of notes, annotations, biographical and background information - Wesley, John, 1703-1791.; Wesley, Charles, 1707-1788.; Rogal, Samuel J. (Lewiston : Edwin Mellen Press, 2010)
This third volume of the ?New Edition? of George Osborn?s nineteenth-century collection of The Poetry of John and Charles Wesley continues to widen the access of the original poems of the eighteenth-century Wesleys, as well as their translations and altered versions of others? poetical works. Although the total of thirteen volumes of Osborn?s edition might justifiably be considered by the scholarly world as ?outdated,? it cannot be termed ?obsolete,? since, nonetheless, it remains as the largest collection of the Wesleys? poetic productions yet published.
Description based upon print version of record.
Keywords: Religious poetry, English -- 19th century; Hymns, English; Wesley, John, -- 1703-1791 -- Poetic works; Wesley, Charles, -- 1707-1788 -- Poetic works; FICTION / General; Electronic books